Exploring communications and media as a means to achieving clinician engagement in “Better for You,” the NUH NHS Trust change programme - Khiroya, Priti (2010)
It is the aim of this study to explore communications which effectively engage clinicians in an organisation wide change initiative for improving safety and quality of patient care. Gaining clinician acceptance of a change management programme is no simple task, but it is possible to find common ground where there are aspects of a safety and quality agenda that can benefit clinicians and patients while also working towards organisation wide objectives. From the large body of literature concerned with change management, clinician engagement and strategic communications, a selection of recommendations for healthcare organisations are analysed for their applicability to the situation at NUH before developing a unique framework intended for use in “Better for You” communications with NUH clinicians. It is found that when used to their full potential, communications can motivate, encourage participation, improve teamwork and facilitate knowledge sharing, but there is no generic formula for an effective communications campaign. It is important to understand the audience, their attitudes, motivations and priorities before developing a campaign that will capture their attention. The research conducted at NUH seeks to understand the organisation culture, the goal alignment between the clinician group and organisation objectives and specifically investigate clinicians’ communication preferences in terms of the method, style, frequency and person to deliver the message. The subsequent recommendations identify patient outcomes as the primary motivator for clinicians, find opportunities for cross functional learning, and list requirements for additional support from the central Communications Department. It is advised to identify and train project champions to lead “Better for You.” “Better for You” should be more prominent in internal publications with commentary from senior management, monthly updates by email and audiovisual intranet posts. Departments should be prepared for “Better for You” through learning logs and face to face meetings with other departments that can share their experience and learnings. Should the recommendations be successfully implemented, clinicians will be better informed and prepared for the “Better for You” change programme, and feel a greater sense of involvement and affiliation with other clinicians also involved in “Better for You.”